Pola Komunikasi Organisasi dalam Membangun Motivasi Kerja Karyawan pada CV Nadhif Engineering - Taro An'umillah; Suparman; Amiruddin Saleh; Rici Haripin; Nabhila Manisya; Anggi Widia; Khalilla Maharani; Maharani Azzahra (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Communication patterns within organizations greatly affect the motivation for employees' work. The research aims to identify and analyze the communication patterns used on nadhif engineering's CV and the effects on employee job motivation. The background of the problem emerged from the observation that employee's work motivation in the company was still low, although companies have implemented various performance improvement programs. The method used is a qualitative approach, with deep interviews and participative observations of employees of various stages. Studies have shown that open, transparent, and participative communication contributes significantly to increased job motivation. Employees feel more appreciated and involved when they are given the opportunity to communicate ideas and feedback. Additionally, management's support in the form of awards and recognition for the contributions of employees has also proven to increase work morale. The study concluded that effective pattern of communication management could be a key strategy in boozing employee job motivation on nadhif engineering, which in turn would contribute to an overall increase in company productivity